Protocol Based Interaction in Component-Based Software Systems. - Alhazbi, Saleh; Jantan, Aman (2007)
In Component-based development, assembling components into systems is the major activity. Therefore, Components must be integrated through well-defined infrastructure. This paper presents a framework for composing component-based systems based on message-pattern interaction among the components; it also presents protocol-based rules to govern messages exchanges.